2015
DOI: 10.12697/bjah.2015.9.09
|View full text |Cite
|
Sign up to set email alerts
|

What is Under the Paint Layer of the Rode Altarpieces?

Abstract: In art research today, technology-based investigation that looks under and into the visible layers of a work of art has assumed an important position alongside the pictorial idiom. With the help of these examinations, information is acquired about the means and methods used to create a work of art and about the position of the work in the general studio practice of a particular artist or period.The focus of the project called "Rode Altarpiece in Close-up" 1 , which was started at the Art Museum of Estonia's Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…the specific attributes of two-and three-dimensional art. The results of previous study demonstrated that complex artefact surveys can be successfully and costeffectively committed [1,2,3,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…the specific attributes of two-and three-dimensional art. The results of previous study demonstrated that complex artefact surveys can be successfully and costeffectively committed [1,2,3,4,5].…”
Section: Introductionmentioning
confidence: 99%